Kinerja Internal Karyawan Bidang Pembudayaan Hukum Di Badan Pembinaan Hukum Nasional - Kesuma, Amirah Rasyidah; Shalahuddin, Shalahuddin (JURNAL MAHASISWA BINA INSANI; Vol 8 No 1 (2023): Jurnal Mahasiswa Bina Insani (Agustus 2023), 2023)
Performance evaluation should be done regularly, structured and written. Internal performance evaluation of employees in the Law Civilizing Division is carried out to improve the quality of employees performance. The purpose of this research is to help create a simple, written and structured performance assesment system. The type of data used in this research is primary data in the form of interviews. The research method used is qualitative. Data collection techniques in this research are through observation and interviews. The results of this study found that the Law Civilizing Division held routine internal performance evaluations that were aside from the ASN assessment but did not yet have written and structured performance assesment standards. So far, internal performance evaluation has been carried out verbally, so that the assessment becomes subjective. In order to make the assessment more objective, this research provides suggestions for the Legal Cultivation Sector, namely by developing a structured and written performance assessment form.